If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-4(5t-2)=7t+3
We move all terms to the left:
-4(5t-2)-(7t+3)=0
We multiply parentheses
-20t-(7t+3)+8=0
We get rid of parentheses
-20t-7t-3+8=0
We add all the numbers together, and all the variables
-27t+5=0
We move all terms containing t to the left, all other terms to the right
-27t=-5
t=-5/-27
t=5/27
| (x-3)+(x+73)+(x+80)=360 | | 45+15+120+120+4x=360 | | 13x+x=90 | | 8(3x-2)=1/2(-32+48x) | | 3/2x-1/6=x+1/4 | | 4b+11=-37 | | 26+x=13+3x | | (x-12)^2=1 | | 9x+1.4=17 | | -22+3/8v=18 | | 1/7x-3=2 | | 10+5n=5(n+2) | | 2x2+3x=275 | | 3x+(x+95)+50+51=360 | | -2=z-11 | | 3x-2=2x=30 | | -5(6x+2)-2=-30x-13 | | 0.02y+0.12=0.04 | | 180=10x+170 | | 9=7v-2v | | -5(5-8m)=10+5m | | 8w-25=-9 | | 3x=x+95 | | 1/2(x+6=18 | | -4(v+3)=-15-4v | | 20=d-78 | | 8x-6=50X= | | 180=2x+102 | | 3x-45=42 | | -9(v-1)=-9v+3 | | 22=4u-14 | | x·6=30 |